Ionization processes in a carbon aerosol upon exposure to long laser pulses. I - Balandin, S. F.; Donchenko, Valeriy A.; Myshkin, V. F.; Potekaev, Aleksandr I. 1951-; Khan, V. A.; Orazymbetova, A. K.; Ospanova, N. A. (Russian physics journal)
The interaction mechanisms of low-energy long-duration (similar to 1 ms) laser pulses with dispersed particles in air are considered. The basic equations describing the mechanisms of particle motion in a plasma flow during heating, thermal emission, and evaporation are formulated. Particular cases of solving equations for prevailing effects of electron evaporation and thermal electron emission from particle surfaces are considered. Data on gas plasma temperature changes upon incorporation of particles with low (similar to 5 eV) and high (similar to 11 eV) ionization potential are presented. Possible chemical reactions in a dispersed carbon medium are analyzed, and their influence on the change of plasma formation energy is shown.